Assessment of knowledge, attitude, and practice of faculty and postgraduates toward Bisphenol A (BPA) exposure in dental care - Bagher, Sara Mustafa; Sabbagh, Heba Jafar; Baik, Alaa Mohammad; Bagher, Amina Mustafa (Journal of the Pakistan Medical Association, 2024)
Bisphenol A (BPA) is commonly used in resin-based dental materials and is categorised as an endocrine-disrupting compound. This study aimed to evaluate the knowledge, attitudes, and practice toward the use of BPA among faculty members and postgraduate students. In this descriptive study, a validated self-administered questionnaire was used, and 204 dentists were included, with a response rate of 56.2%. The findings revealed that faculty members had significantly better knowledge (P=0.024) and practice (P=0.036) and more positive attitudes (P=0.024) toward BPA exposure. Regression analysis showed a significantly positive effect of attending a workshop/lecture or reading an article about BPA on the participants’ total mean knowledge (P<0.001) and practice scores (P<0.001). Furthermore, faculty members showed a significantly more positive attitude (P<0.001) toward BPA exposure. These results emphasise the importance of increased awareness and education concerning BPA exposure to ensure optimal dental care. Keywords: Attitude, Bisphenol A-Glycidyl Methacrylate, Composite resins, Knowledge, Professional practice.